Foehn Event Triggered by an Atmospheric River Underlies Record‐Setting Temperature Along Continental Antarctica. Issue 8 (21st April 2018) - Bozkurt, D.; Rondanelli, R.; Marín, J. C.; Garreaud, R.
Abstract: A record‐setting temperature of 17.5°C occurred on 24 March 2015 at the Esperanza station located near the northern tip of the Antarctic Peninsula (AP). We studied the event using surface station data, satellite imagery, reanalysis data, and numerical simulations. The Moderate Resolution Imaging Spectroradiometer Antarctic Ice Shelf Image Archive provides clear evidence for disintegration and advection of sea ice, as well as the formation of melt ponds on the ice sheet surface at the base of the AP mountain range. A deep low‐pressure center over the Amundsen‐Bellingshausen Sea and a blocking ridge over the southeast Pacific provided favorable conditions for the development of an atmospheric river with a northwest‐southeast orientation, directing warm and moist air toward the AP, and triggering a widespread foehn episode. A control simulation using a regional climate model shows the existence of local topographically induced warming along the northern tip of the AP (∼60% of the full temperature signal) and the central part of the eastern AP (>90% of the full temperature signal) with respect to a simulation without topography. These modeling results suggest that more than half of the warming experienced at Esperanza can be attributed to the foehn effect (a local process), rather than to the large‐scale advection of warm air from the midlatitudes. Nevertheless, the local foehn effect also has a large‐scale advection component, since the atmospheric river provides water vapor for orographic precipitation enhancement and latent heat release, which makes it difficult to completely disentangle the role of local versus large‐scale processes in explaining the extreme event. Key Points: This study examines the local and large‐scale forcing of Antarctic continental temperature record through observation and modeling experiments We attribute ∼60% of the warming at the Esperanza station directly to the foehn effect rather than the advection of warm air from midlatitudes At the same time, the widespread foehn episode was triggered by the large‐scale moisture advection associated with an atmospheric river